1995
DOI: 10.3386/w5165
|View full text |Cite
|
Sign up to set email alerts
|

Leverage, Investment, and Firm Growth

Abstract: CLQqW !ucJflcl!u © UOPW 12 1AQU 1O JJC 2OflLC uoj o cxccq r!io b1. .bp2 urnA pc dnocq iiponr ccbjc bCLW!22!OU bz.oAqcq wi ii'ii © pA r'u.A ru El! ()I,GJC uq JC1J 'f 2WW VJJ LU2 LG2CLAGq JOL 2GCOU2 Oj 1GXI O IJJC 4UOIJ91 BflLCf1 O ECOUOWIC JC2CVLCJJ h4c!u uq COthOL jjuucc iA ob!1J!ou2 cxbLG22cq i.c ipoc oj qi r1poT.2 mJq uo ipoc flhJ1ACL2A uq ØpiO 2W1C flU!ACL2!A j.p bbci a b91.j 0 14BEK2 LC2G91CJJ bLouJ2 u Jf1pCJc1 vuqic! 2PIC!L 911 ØUOUAWOfl2 CCIC UIJq b914!C!b91112 9 2UJUL2 9 M A04C JC LGJ1J OL COWUJCUI2 pOW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
420
5
28

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(497 citation statements)
references
References 12 publications
44
420
5
28
Order By: Relevance
“…The results of the paper indicate that leverage has a significantly negative impact on investment for Canadian firms and that it has a stronger negative impact on firms with low growth opportunities. Our results are similar to earlier ones for the US, such as those of Lang et al (1996). This paper utilizes the instrumental variable approach to address the endogeneity problem pertaining to the relationship between leverage and investment.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the paper indicate that leverage has a significantly negative impact on investment for Canadian firms and that it has a stronger negative impact on firms with low growth opportunities. Our results are similar to earlier ones for the US, such as those of Lang et al (1996). This paper utilizes the instrumental variable approach to address the endogeneity problem pertaining to the relationship between leverage and investment.…”
Section: Introductionsupporting
confidence: 87%
“…They show that corporate value is negatively correlated with leverage for firms with strong growth opportunities (indicated by high Tobin's Q), and positively correlated with leverage for firms with weak growth opportunities (or low Tobin's Q). Their results are consistent with the hypothesis that 2 See Lang et al (1996). 3 Alternatively, if transaction costs of bargaining are small, recontracting between debt holders and equity holders internalizes potential externalities generated by leverage, in effect overcoming the underinvestment problem.…”
Section: The Link Between Leverage and Investmentsupporting
confidence: 61%
See 1 more Smart Citation
“…These studies have analysed firm-level data and found relationships between employment and variables such as size (Broersma & Gautier, 1997;Hall, 1987;Oliveira & Fortunato, 2006;Singh & Whittington, 1975), age (Audretsch, 1995;Broersma & Gautier, 1997;Jovanovic, 1982;Oliveira & Fortunato, 2006), leverage (Carpenter & Petersen, 2002;Fazzari, Hubbard, &Petersen, 1988, Heisz andLaRochelle-Côté, 2004;Lang, Ofek, & Stulz 1996;Yazdanfar, 2011), liquidity (Acemoglu, 2001;Funke, Maurer, Siddiqui, & Strulik, 1998;Winker, 1999). Since firm size and age have an influence on information asymmetry, they are relevant when studying liquidity constraints (Myers, 1984;Myers & Majluf, 1984).…”
Section: The Independent Variablesmentioning
confidence: 99%
“…As mentioned above, unlike much previous research, this study is based on the resource-based approach, implying that the independent firm-level variables, size, age, leverage and liquidity, positively influence job creation (Audretsch, 1995;Autio, 2005;Hall, 1987;Lang, Ofek, & Stulz 1996).…”
Section: Hypothesesmentioning
confidence: 99%